IMPLEMENTASI PROGRAM OPPORTUNITIES FOR VULNERABLE CHILDREN (OVC) TERHADAP SISTEM PENDIDIKAN INKLUSIF BAGI ANAK DISABILITAS DI INDONESIA OLEH HELEN KELLER INTERNATIONAL (HKI) TAHUN 2010 – 2013 - Sari, Rizka Kumala; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study of contemporary which discussing about implementation of Opportunities for Vulnerable Children (OVC) program by Helen Keller International (HKI). Education is a basic human right and a significant factor in the development of children, communities, and countries. Everyone has the right to education but for Children with disabilities, it is difficult to get access to education. Disability education has become one of the international issues at at Convention on the Rights of the Child in 1989 and The International Conference on special education in 1991 which led to the term “Education For All” and The Salamanca World Conference on Special Needs Education in 1991. In 2003 Indonesia invites HKI to develop an inclusive education system for child with disability in Indonesia with Opportunities for Vulnerable Children (OVC) program. In effort to implementation of OVC program, HKI faced some obstacles. The lack of policies on inclusive education system at the Province and District, lack of teachers of special education and lack of knowledge of the Government and communities about the concept of inclusive education system and child with disability.Keywords : Inclusive education, Disability, Helen Keller International (HKI), Opportunities for Vulnerable Children (OVC).